Effectiveness Service Guidance And Counseling in Overcome Behavior Bullying at School - Cipa Purnama Sari; Yarmis Syukur; Dina Sukma (Yayasan Darussalam Bengkulu, 2025)
Bullying is an aggressive act involving a power imbalance that significantly impacts both victims and perpetrators. This study explores the role of guidance and counseling (BK) services in addressing bullying through individual and group counseling, techniques like the Structured Learning Approach (SLA), and bibliotherapy. Additionally, BK services play a critical role in raising awareness among students, teachers, and parents through information programs and anti-bullying campaigns. This research employs a literature review method, analyzing relevant journals and studies published between 2017 and 2024. The analysis was conducted using keywords such as